Influence of artificial sebum on the dermal absorption of chemicals in excised human skin: A proof-of-concept study - Schneider, Daniela; Dennerlein, Kathrin; Göen, Thomas; Schaller, Karl-Heinz; Drexler, Hans; Korinth, Gintautas (Toxicology in Vitro, 2016)
In an initial diffusion cell study, the influence of artificial sebum on dermal penetration and intradermal reservoir of ethanol and toluene was investigated in comparison with the effects of a skin cream (o/w- and w/o-emulsion) and untreated (control) skin. Human skin was exposed to neat ethanol and toluene for 4h, respectively. During the experiments, the penetration of the compounds was assessed in the receptor fluid. The amounts of the test compounds in the skin were determined at the end of exposure. In the control experiments, 42% of the total resorbed ethanol amounts were found in the intradermal reservoir after 4h, whereas 82% of the toluene amounts were found in the skin compartments. The treatment with artificial sebum showed no significant differences in dermal absorption of both test compounds compared to control skin. In contrast, the treatment with skin cream increased the percutaneous penetration (p<0.001) and the intradermal reservoir of ethanol 2-fold but not of toluene. In all exposure scenarios, a relevant intradermal reservoir was formed. The results indicate that sebum does not influence the percutaneous penetration and the intradermal reservoir of epidermally applied chemicals, whereas the application of skin creams may increase the dermal penetration of the compounds.
EVALuna2:9746